Effect of Eugenol on Streptococcus mutans Adhesion on NiTi Orthodontic Wires: In Vitro and In Vivo Conditions - Fatene, Nassiba; Mounaji, Khadija; Soukri, Abdelaziz (European Journal of General Dentistry, 2021)
Objective The purpose of this study was to compare the antibacterial effect of two types of Eugenol against Streptococcus mutans and then assess the effect of different concentrations of two types of Eugenol on S. mutans adhesion on Nickel-Titanium (NiTi) orthodontic wires in comparison to in vivo wires with fluoride-based hygiene regimen.Materials and Methods Culture of Streptococcus mutans with NiTi orthodontic wires was done. Different media were prepared by adding 100%, 50%, 25%, and 12.5% of two origins of Eugenol (one biological obtained by hydrodistillation of Syzygium aromaticum and one chemical already prepared available in drugstores for dental use (Idental, MOROCCO, lot number: UAN/17–211/1). Three sizes of NiTi wires (0.016 inch, 0.016 × 0.022 inch, 0.017 × 0.025 inch) were retrieved from adult patients undergoing orthodontic treatment after 1 month of setting them up in the mouth. After incubation, colony forming unites were calculated and a SEM analysis was done to the surface of each wire. ANOVA test was done between all groups to find statistical differences and post-hoc t-test with Bonferroni analysis was performed to elucidate differences between all groups with α = 0.05.Results Eugenol has an anti-bacterial effect against S. mutans. The biological Eugenol has greater effect than the chemical one. The same observations were done for anti-adherent effect, the biological Eugenol demonstrated the highest anti-adherent effect at all concentrations while the effect of the chemical Eugenol was the lowest.Conclusions The origin and the extraction mode of Eugenol have a crucial role in its antimicrobial and anti-adherent effect. Eugenol might constitute an alternative to Fluoride because it has an anti-adherent effect, limiting the incidence of white spot lesions.
Keywords: Nickel-Titanium; Streptococcus mutans; bacterial adhesion; Eugenol; Orthodontic wires